2019
DOI: 10.1038/s41467-019-12030-x
|View full text |Cite
|
Sign up to set email alerts
|

An ultrahigh resolution pressure sensor based on percolative metal nanoparticle arrays

Abstract: Tunneling conductance among nanoparticle arrays is extremely sensitive to the spacing of nanoparticles and might be applied to fabricate ultra-sensitive sensors. Such sensors are of paramount significance for various application, such as automotive systems and consumer electronics. Here, we represent a sensitive pressure sensor which is composed of a piezoresistive strain transducer fabricated from closely spaced nanoparticle films deposited on a flexible membrane. Benefited from this unique quantum transport … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
96
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(97 citation statements)
references
References 51 publications
1
96
0
Order By: Relevance
“…Approximately ten times higher sensitivities were reported by Chen et al. [ 48 ] for resistive pressure sensors employing palladium nanoparticles deposited onto polymer diaphragms as strain sensitive transducers. However, these sensors featured significantly larger diaphragms (19.6 × 10 6 μm 2 ) compared to approximately 4 × 10 4 μm 2 membranes used in our study.…”
Section: Resultsmentioning
confidence: 79%
“…Approximately ten times higher sensitivities were reported by Chen et al. [ 48 ] for resistive pressure sensors employing palladium nanoparticles deposited onto polymer diaphragms as strain sensitive transducers. However, these sensors featured significantly larger diaphragms (19.6 × 10 6 μm 2 ) compared to approximately 4 × 10 4 μm 2 membranes used in our study.…”
Section: Resultsmentioning
confidence: 79%
“…Apart from the rapid development demonstrated in this review, there is a bright future for tactile sensors utilizing smart materials (e.g., piezoelectric, self-healing, self-powering, self-cleaning), additive manufacturing, big data analytics (e.g., artificial intelligence) and cloud computing to fulfill healthcare demand for personalized medicine and remote monitoring. We found that sensitivity was the focus for most of the developed devices [247][248][249]251,[257][258][259][260][274][275][276][277][278][279][280][281][282][283][284][285] and those with piezoresistive mechanisms generally showed high performance when compared with others [242,259,271,283,293]. Although piezocapacitive-based sensors still show excellent detectability and sensitivity, they are more susceptible to noise resulting from field interaction and fringing capacitance, as well as, other factors such as temperature [192,247,294,614].…”
Section: Discussionmentioning
confidence: 97%
“…However, this gauge factor is less than that of a nanocomposite, for instance, made of MoS2/GF/Ecoflex [284]. Although this woven structure, as a strain sensor, shows acceptable linearity and sensitivity, it shows a hysteresis of a maximally 4.6% difference during stretching and releasing, whereas, a pressure sensor based percolative metal NPs arrays with Ag IDEs shows an insignificant level of hysteresis induced by a 1KPa applied pressure while maintaining a limit of detection and a sensitivity of 0.5 Pa and 0.13 kPa −1 , respectively [248].…”
Section: Electrodesmentioning
confidence: 97%
See 1 more Smart Citation
“…[23][24][25][26] The latter category has received the highest attention, as piezoresistive devices are widely utilized as strain gauges and tactile sensors. [27][28][29] Strain gauges made of single crystalline silicon and germanium are commercially available, [30,31] but these devices are expensive and difficult for mass integration which is required for the fabrication of large 2D arrays demanded for exponentially growing biomedical applications and man/ machine interfaces. [32][33][34][35][36][37] While the quantitative predictions on the operational features of single crystalline piezoresistive devices involve high rank tensorial deliberations, [38] simple scalar calculations are usually sufficient for similar considerations in the polycrystalline or composite materials, such as those utilized for fabricating low cost touchpads.…”
Section: Pressure Sensitivity Of Charge Conduction Through the Interfmentioning
confidence: 99%